2013
DOI: 10.12669/pjms.296.3863
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Lipid levels as a risk factor of eclampsia, study conducted in tertiary care Hospitals of Khyber Pakhtunkhwa Province - Pakistan

Abstract: Objective: To evaluate abnormal lipid metabolism as a risk factor of eclampsia in pregnant women. Methods: This cross sectional study was conducted in three tertiary care hospitals of Peshawar. Serum total cholesterol (TC), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), very low density lipoprotein cholesterol (VLDL-C), triglyceride (TG), apolipoprotein A1 (APO-A1), APO-B100, lipoprotein-a (Lpa) were measured in 110 women with eclampsia and compared with 90 healthy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In agreement with our study, few studies had demonstrated that the higher Lp(a) levels were associated with severity of disease. [27][28][29] This increase might be due to more widespread endothelial cell damage, necessitating increased levels of Lp(a) to act both as an acute phase protein and as a vehicle for cholesterol deposition at the site of dysfunction. 30 However some studies had demonstrated no change in the level of Lp (a), this might be due to the differences in the method used, study design, sample sizes and ethnicity of study population.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our study, few studies had demonstrated that the higher Lp(a) levels were associated with severity of disease. [27][28][29] This increase might be due to more widespread endothelial cell damage, necessitating increased levels of Lp(a) to act both as an acute phase protein and as a vehicle for cholesterol deposition at the site of dysfunction. 30 However some studies had demonstrated no change in the level of Lp (a), this might be due to the differences in the method used, study design, sample sizes and ethnicity of study population.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Musleh Uddin et al 12 in 2012 had mean systolic blood pressure of 154 ± 0.55 mmHg and diastolic blood pressure of 102 ± 0.73 mmHg while in our study the mean systolic blood pressure was similar at 170 ± 11 mmHg and diastolic blood pressure was 108.9 ± 7.09 mmHg. According to a study done by Rubina Nazli et al 5 in 2013, the mean cholesterol level in eclamptic patients was higher (216.63 ± 5.17 in cases compared with 202.23 ± 4.6 in controls). Our study also showed a definite rise in serum cholesterol in eclamptics (mean 301.85 ± 26.65) compared with controls (215.53 ± 19.10).…”
Section: Table 26 Systolic and Diastolic Bp Of Eclamptic Patientsmentioning
confidence: 94%
“…Significantly elevated plasma concentration of triglycerides (TG), phospholipids and total lipids and decreased high density lipoprotein -cholesterol (HDL-C) concentrations were found in women with eclampsia in comparison to normal pregnancy. 5,6,7,8…”
mentioning
confidence: 99%
“…It is a pregnancy-specific disease affected 3–5% of women globally and is documented as one of the major causes of maternal and neonatal morbidity, mortality and stillbirths [ 4–6 ]. In our country, nearly 19% of maternal mortality is credited to preeclampsia [ 4 , 7 ]. Due to unreliable prognosis and diagnosis of preeclampsia, its management is a challenging task [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%